x-3-6x=-3x-7+5x

Simple and best practice solution for x-3-6x=-3x-7+5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-3-6x=-3x-7+5x equation:


Simplifying
x + -3 + -6x = -3x + -7 + 5x

Reorder the terms:
-3 + x + -6x = -3x + -7 + 5x

Combine like terms: x + -6x = -5x
-3 + -5x = -3x + -7 + 5x

Reorder the terms:
-3 + -5x = -7 + -3x + 5x

Combine like terms: -3x + 5x = 2x
-3 + -5x = -7 + 2x

Solving
-3 + -5x = -7 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
-3 + -5x + -2x = -7 + 2x + -2x

Combine like terms: -5x + -2x = -7x
-3 + -7x = -7 + 2x + -2x

Combine like terms: 2x + -2x = 0
-3 + -7x = -7 + 0
-3 + -7x = -7

Add '3' to each side of the equation.
-3 + 3 + -7x = -7 + 3

Combine like terms: -3 + 3 = 0
0 + -7x = -7 + 3
-7x = -7 + 3

Combine like terms: -7 + 3 = -4
-7x = -4

Divide each side by '-7'.
x = 0.5714285714

Simplifying
x = 0.5714285714

See similar equations:

| (3x-2)(3x-2)=15 | | 4y^2+9u+2=0 | | 7x+8=x+32 | | 14y+16=48-15+18 | | 3/8(x-4)=24 | | y=17+-7x | | y=x^2+7x-2 | | -8xy+-12xy= | | 1/2x-3=14/5-3/4x | | 17f^2+7f=0 | | 2=0.6x^2+3x+4 | | 12x-10=12-4x | | u-3+10u+6=102 | | 0=0.6x^2+3x+6 | | 1/4y-6=1/10y | | 2(x+2)=85 | | 20x-2=12x+7 | | 5(10x+25)=575 | | -96=4u-10-27u+6 | | x/-0.168=0.08 | | 3/5w=8/9 | | 2x-3(5-x)=20 | | 2x-3(x-5)=20 | | -1.68/x=-0.08 | | 128+112x-16x^2=0 | | (x+7)(x-1)(2x+1)(x-3)=8 | | -0.168/x=-0.08 | | 5x-3(x-2)=-6+4x+4 | | -1.68/x=0.08 | | 360/6x5 | | x-11+4x+4=3x+5+2x-12 | | (x+7)(x-1)(2x+1)(x-3)=0 |

Equations solver categories